NEONATAL APPENDICITIS WITH NECROTIZING ENTEROCOLITIS - Aslam, Yumna; Hasan, Hania; Mirza, Adnan; Ali, Amin; Muhammad S. Salat; Qamar, Mohammad Aadil (Journal of Ayub Medical College Abbottabad, 2022)
Acute appendicitis is an infrequent condition in neonates, especially in term infants. With around 100 cases in the last century and no specific diagnostic tool, this case report is an addition to the existing literature that helps in our understanding of the disease. A preterm infant who had greenish aspirates and dilated bowel loops on abdominal x ray and was treated on the lines of necrotizing enterocolitis failed to improve. Baby had issues of abdominal distension whenever feeds were started hence exploratory laparotomy was done on the 45th day of life which showed appendicitis with adherent terminal ileum, caecum, and appendix. Two months after the surgery, the patient was unable to respond to antibiotic therapy for septic condition leading to death.